EUROPEAN ASH HEALTH CONDITION IN THE FOREST-STEPPE PART OF SUMY REGION - Meshkova, V. L.; Borysova, V. L.; Skrylnik, Yu. Ye.; Zinchenko, O. V. (Forestry and Forest Melioration, 2018)
Introduction European ash (Fraxinus excelsior L.) is one of the most spread tree species in broadleaved forests of the Left-Bank Forest Steppe of Ukraine. In recent years the health condition of European ash has worsened in many European countries. In previous years in permanent sampling plots in Kharkiv region eight types of damage were detected in inspected European ash stands, namely frost cracks, mechanical damage of stems, epicormic shoots, branch dieback, symptoms of bacterial disease and butt rot, signs of wood destroying fungi and insect feeding. Their occurrence in different forest site conditions and depending on stand age was evaluated. However, the relations of particular symptoms of ash health worsening with health condition index were not studied. The aim of the research was to evaluate different symptoms of European ash health condition and their relations in the forest-steppe part of Sumy region. Materials and Methods Survey of 62 forest plots with European ash participation was carried out in 2018 in the State Enterprise "Trostyanets Forest Economy" (SE "Trostyanets FE"). Occurrence (incidence) of each type of damage was evaluated as the proportion of trees with respective symptoms or signs. The severity of each type of damage as well as tree health condition was estimated using respective scores. Crown defoliation and proportion of dry branches were estimated as a percentage and then converted to points: 0 – absent; 1 point – up to 10 %; 2 points – 11–50 %; 3 points – 51–75 %; 4 points – over 75 %. The severity of epicormic shoots was estimated by the following score: 0 – absent; 1 – single; 2 – multiple; 3 – completely covered stem. Category of the health condition of European ash was evaluated on a range of visual characteristics (the crown density and colour, the presence and proportion of dead branches in the crown, etc.) according to the Sanitary rules in the forests of Ukraine. The statistical analyses were carried out using software MS Excel, particularly for descriptive statistics, analysis of variance (ANOVA) as well as a correlation between particular parameters of tree health condition. Results and Conclusions The average health condition index of European ash (Fraxinus excelsior L.) in inspected stands of the State Enterprise “Trostyanetske Forest Economy” is 2 points. European ash mortality was the highest in Krasnyanske Forestry (0.8 % and 3.5 % of recently died trees and the trees died over a year ago respectively). The highest proportion of healthy European ash trees was inspected in Makivske and Krasnyanske Forestries (85.3 % and 50.1 % respectively). The trees of European ash of the 1st category of health condition can be reliably distinguished from the trees of other categories of health condition. Total score of “0” for all parameters of health condition (defoliation, dieback, and epicormic shoots occurrence) reliably points at a healthy tree. Trees can be assigned to the 1st category of health condition with defoliation caused by insects up to 50 % and with up to 10 % of dry branches and single epicormic shoots. Multiple epicormic shoots are characteristic for the trees of the 3rd category of health condition. Ambiguous results in distinguishing of European ash trees of the 2nd and the 3rd, the 3rd and the 4th categories of health condition confirm the necessity to improve its assessment and annual monitoring of the forest health at key plots. 5 Figs, 3 Tables, 13 Refs.